2022
DOI: 10.20525/ijrbs.v10i7.1446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of memorable tourism experience on tourist’s satisfaction and revisiting

Abstract: In the context of cittaslow (slow city), this research attempts to examine the effects of memorable tourism experience (MTE) on tourist satisfaction and revisiting intention. The research used a structured questionnaire and collected 605 valid responses from tourists that visited Sanyi Cittaslow. Analyses of the measurement model and structural model by AMOS 22.0 were used to find the associations between each MTE dimension and satisfaction, and revisit intention. Test results revealed that all MTE dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In an empirical study on Caribbean tourists, their satisfaction experience has a remarkable positive impact on revisit intention (Petrick, 2004). Another study showed that all dimensions of unforgettable travel experience are predictors of tourist satisfaction (Tsai et al, 2021). Hence, this study proposes the following hypothesis:…”
Section: The Relationship Between Travel Experience Place Attachment ...mentioning
confidence: 84%
“…In an empirical study on Caribbean tourists, their satisfaction experience has a remarkable positive impact on revisit intention (Petrick, 2004). Another study showed that all dimensions of unforgettable travel experience are predictors of tourist satisfaction (Tsai et al, 2021). Hence, this study proposes the following hypothesis:…”
Section: The Relationship Between Travel Experience Place Attachment ...mentioning
confidence: 84%
“…Destination Type [14,19] Honeymoon tourism [8,10,15,18,30] Natural tourism [10,16,27] Culture tourism [17,20] Rural tourism [21] Yoga tourism [22,24] Urban tourism [23,29] Religious tourism [11] Health tourism [28] Event tourism of various factors found in tourism destinations that attract travelers to choose these destinations. On the other hand, according to [31], destination attributes refer to the factors that influence a traveler's decision to select one destination over another after the decision to travel has been made.…”
Section: Researchersmentioning
confidence: 99%
“…Psychologically, new feelings that come from new experiences are the meaning of novelty [28]. Constant novelty is listed as another key factor in subjective travel experiences and a prevalent motivation for someone to travel [29]. Novelty-seeking behavior can reflect tourists' preference for new experiences and is generally known as a personality trait that is stable and consistent over time.…”
Section: Introductionmentioning
confidence: 99%